MARKETING COMMUNICATION STRATEGIES TO IMPROVE TOURISM IN SARI ATER RESORT HOTEL - Arnold Yudi Nanholy; Adinda Yuliani (Jurnal Inovasi Penelitian, 2022)
Located in Subang Regency, Sari Ater is a major tourist attraction. Subang Regency's tourism potential is also supported by good accessibility and transportation infrastructure. In conducting a descriptive study of the object of writing, the author uses a qualitative method, which is suitable for searching the social and communication fields in particular. To better understand the psychological aspects, behavior, attitudes, responses, opinions, feelings, and desires of a person or group. The results of this study, the strategy of messaging the content of communication information regarding rates, prices, services, and facilities is delivered based on health protocols. The creative form of the message is conveyed in the form of a rational and emotional message. In the media strategy, Sari Ater selects social media, then chooses Instagram as a means of marketing communication. Sari Ater determines the best time and location to share messages with the audience so that it becomes a gap to attract consumers. In the conclusion of this study, there is a change in the marketing communication strategy on Instagram owned by Sari Ater hotels & resorts.